Role of IL-6 in the immunopathogenesis of mild, moderate and severe TBI - A. O. Norka; S. V. Vorobyev; R. N. Kuznetsova; S. V. Lapin; Z. R. Korobova; D. N. Monashenko; Areg A. Totolian (Медицинская иммунология, 2023)
Traumatic brain injury (TBI) results in a significant inflammatory burden that increase the production of inflammatory mediators and biomarkers. The immune system plays a key role in the pathogenesis of traumatic brain injury. Neuroinflammatory mediators released from resident glia (activated microglia and astrocytes) inside the brain recruit immune cells where cytokines are small soluble proteins that confer instructions and mediate communication among immune and non-immune cells. Interleukin-6 (IL-6) is a proinflammatory cytokine known to be elevated after trauma, and a major contributor to the inflammatory response following TBI. Previous studies have investigated associations between IL-6 and outcome following TBI, but to date, studies have been inconsistent in their conclusions. The purpose of the current study was to assessment of cerebrospinal fluid (CSF) interleukin-6 (IL-6) and MBP levels in patients with TBI. Samples of cerebrospinal fluid of 85 patients with TBI were examined. Concentrations IL-6 were measured via xMAP multiplexing technology. The control was the course of CSF in patients with concussion. An increased content was found in all patients with traumatic brain injury: 19.59 pg/mL in the group with mild traumatic brain injury; 103.6 pg/mL in the group with moderate traumatic brain injury; and 2225 pg/mL in the group with severe traumatic brain injury load versus 2.58 pg/mL in the control group. A direct correlation was found with the presence of basic myelin proteins in the cerebrospinal fluid, which indicates the degree of damage and neurodegeneration processes. Identification of the features of IL-6 content in patients with brain injury may indicate its important role in the course of disease. It also requires additional more detailed study, including comparison with IL-6 content in peripheral blood.